Fatal early-onset checkpoint inhibitor pneumonitis in a patient with advanced squamous-cell lung cancer with underlying pulmonary fibrosis: a case report and review of the literature - Keller, Daria M.; Żarczyński, Dagobert; Rybacka, Anna; Kuźnar-Kamińska, Barbara (Frontiers in Oncology, 2025)
IntroductionWe report a case of fulminant checkpoint inhibitor pneumonitis (CIP) occurring after a single dose of immune checkpoint inhibitor (ICI) therapy in a patient with advanced non-small cell lung cancer and underlying fibrotic interstitial lung disease (ILD), illustrating a rare but clinically significant and often fatal immune-related adverse event.Main symptoms and clinical findingsA 78-year-old woman with stage IVb squamous-cell carcinoma of the lung and idiopathic pulmonary fibrosis (IPF) developed progressive dyspnea, hypoxemia, and systemic inflammation shortly after receiving her first dose of pembrolizumab. High-resolution computed tomography (HRCT) revealed new bilateral ground-glass opacities superimposed on a fibrotic background with a definite usual interstitial pneumonia (UIP) pattern.Diagnoses, interventions, and outcomesFulminant early-onset CIP was diagnosed after exclusion of infectious causes. Despite discontinuation of immunotherapy and escalation of immunosuppressive treatment—including high-dose corticosteroids, mycophenolate mofetil, and infliximab—the patient’s respiratory status deteriorated, resulting in death 27 days after treatment initiation.ConclusionThis case illustrates that life-threatening CIP can occur after a single dose of ICI in patients with fibrotic ILD. It emphasizes the urgent need for risk-adapted treatment strategies and enhanced monitoring protocols in this high-risk population.